Usability Of Web-Based Real Time Customer Support System In Malaysia - Fatt, Leong Kam (2001)
In this paper, we have examined the usability of the Web-based real time customer interaction system in Malaysia e-commerce environment regarding the different aspects of system's relevance and efficiency, customers' attitude and learnability (REAL) as a